HUMANITAS DAN OTONOMI MORAL DALAM PENDIDIKAN: REFLEKSI KANTIAN ATAS FENOMENA CYBERBULLYING - Losianus Harjon; Henok Albert Ware Mere; Yohanes Risaldo Fallo; Gregorius Sila; Martinus Suni; Petrus Dewantara Brliant Egus (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The phenomenon of cyberbullying is increasingly prevalent and has serious impacts on individuals’ psychological and moral conditions, especially among adolescents. This study aims to analyze cyberbullying through the perspectives of humanity and moral autonomy based on the thought of Immanuel Kant. The method used is qualitative-descriptive with a literature study approach. The results show that cyberbullying contradicts Kant’s categorical imperative, which emphasizes respect for human dignity and actions based on universal principles. Low levels of digital literacy and ethical awareness are the main factors contributing to this behavior. In conclusion, addressing cyberbullying requires not only legal approaches but also the strengthening of moral education and digital ethics to build a more responsible and civilized society.